2014
DOI: 10.3109/15563650.2014.954125
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reducing the threshold for acetylcysteine treatment in acute paracetamol poisoning: The recent United Kingdom experience

Abstract: Changes to national guidelines for managing paracetamol poisoning in the UK have increased the numbers of patients with acute overdose treated with acetylcysteine, with most additional treatments occurring in patients in the 100-149 mg/L dose range, a group at low risk of hepatotoxicity and higher risk of adverse reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 9 publications
1
7
0
2
Order By: Relevance
“…This “150 line” on the Rumack-Matthews nomogram is a level imposed by FDA to ensure as many patients as possible are treated without increasing the risk of overtreatment and the attendant costs of therapy. [68, 70] In other nations, such as the U.K., the threshold plasma concentration was lowered to 100 mg/L in 2012 [71] This change in national guidelines resulted in an increased proportion of patients being admitted and treated with NAC, most of whom presented with concentrations between 100 and 149mg/L. However, the change was not associated with any increase in adverse reactions to NAC.…”
Section: Specific Antidotes To Treat Dilimentioning
confidence: 99%
See 1 more Smart Citation
“…This “150 line” on the Rumack-Matthews nomogram is a level imposed by FDA to ensure as many patients as possible are treated without increasing the risk of overtreatment and the attendant costs of therapy. [68, 70] In other nations, such as the U.K., the threshold plasma concentration was lowered to 100 mg/L in 2012 [71] This change in national guidelines resulted in an increased proportion of patients being admitted and treated with NAC, most of whom presented with concentrations between 100 and 149mg/L. However, the change was not associated with any increase in adverse reactions to NAC.…”
Section: Specific Antidotes To Treat Dilimentioning
confidence: 99%
“…However, the change was not associated with any increase in adverse reactions to NAC. [71] In Hong Kong, Chan et al[70] reported that only 21% of 893 patients presented with an overdose concentration above the 150 treatment line threshold, with 12.5% having serum levels between 100 and 150ug, and 66.5% were below the 100ug treatment line. They cautioned that while lowering the treatment line to 100ug would cut the NAC failure rate from 0.45% to 0.22%, it needs to be balanced against a higher incidence of anaphylactoid reactions and increased costs.…”
Section: Specific Antidotes To Treat Dilimentioning
confidence: 99%
“…The UK position differs from international guidance (the United States and Australia use higher ingestion thresholds to trigger treatment 17 18 ) and may need revisiting because a substantial increase in the number of patients admitted to hospital for treatment has been reported since the guidance changed. 19 A review could identify new measures to reduce the incidence of therapeutic overdose and reduce the number of low risk patients being unnecessarily treated with a time consuming antidote that commonly produces adverse reactions and results in substantial hospital bed occupancy.…”
Section: Editorials How Many Tablets Do I Take?mentioning
confidence: 99%
“…At present, few data exist concerning the impact on rates of occurrence of liver injury or adverse acetylcysteine effects. Early reports from the UK indicate that, since September 2012, there have been increased numbers of patients receiving acetylcysteine, increased hospitalisation and a substantial financial burden (Thompson et al 2013; Bateman et al 2014a). …”
Section: Introductionmentioning
confidence: 99%